2022
DOI: 10.3390/vaccines10071156
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness of Polish Parents on Vaccination against Human Papillomavirus

Abstract: Background: Human papillomavirus (HPV) vaccinations are rare among Polish children, and the reasons are scant. The objective was to evaluate the knowledge, attitude and awareness of parents about HPV vaccination to investigate reasons for low HPV vaccination coverage. Methods: 387 parents of children hospitalized at the Children’s Hospital were asked to participate in an anonymous and voluntary survey study. Three hundred and two surveys were returned. Results: Only 54% of participants have heard about HPV, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(35 citation statements)
references
References 31 publications
0
34
1
Order By: Relevance
“…Older studies showed that parents tended to postpone HPV vaccination as they associate HPV vaccination with sexual life or the hesitancy of medical recommendations for an early HPV vaccination [ 30 ]. One study from Poland revealed that Polish parents have a positive attitude towards vaccination; however, only 5% of daughters and 4% of sons were vaccinated against HPV in Poland [ 31 ], compared with our data, where more parents vaccinated their children. In our study out of 666 parents, 67 (10.06%) parents vaccinated their children, both girls and boys, against HPV.…”
Section: Discussioncontrasting
confidence: 88%
“…Older studies showed that parents tended to postpone HPV vaccination as they associate HPV vaccination with sexual life or the hesitancy of medical recommendations for an early HPV vaccination [ 30 ]. One study from Poland revealed that Polish parents have a positive attitude towards vaccination; however, only 5% of daughters and 4% of sons were vaccinated against HPV in Poland [ 31 ], compared with our data, where more parents vaccinated their children. In our study out of 666 parents, 67 (10.06%) parents vaccinated their children, both girls and boys, against HPV.…”
Section: Discussioncontrasting
confidence: 88%
“…A systematic search was performed in four databases on 13 September 2023, resulting in 9322 articles; after removing the duplicates, 4206 publications were screened by title and abstract. In total, 133 were assessed for full-text, and 25 [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] were included in the systematic review and meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were included in the meta-analysis of parents’ gender (comparing fathers and mothers), with 18,890 responders, of whom 13,983 had vaccinated (or an intent to vaccinate their) children [ 17 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The results revealed an OR of 0.75, with a 95% CI between 0.54 and 1.04, at a Z of 1.71 and a p = 0.09; Random Effects (RE) were used for an I 2 of 89% (See Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has not been possible to achieve a satisfactory effect so far and further efforts are being performed to increase HPV-vaccination coverage. Information campaigns and free vaccination campaigns organized by local governments are receiving positive responses from the public, as emphasized especially by Polish parents [ 23 ]. Therefore, additional nationwide efforts are needed to transfer the success of the vaccination program to the entire population.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to further analyze the awareness and attitudes of physicians in order to raise the level of HPV vaccination in Poland. This is additionally important because the public is positively disposed to vaccination, while there is inadequate awareness of the need [ 23 , 35 ]. The public trusts doctors, so overcoming the problems outlined by professionals should be thoroughly researched and solved in the future.…”
Section: Discussionmentioning
confidence: 99%